Light metals on oxygen-terminated diamond (100): Structure and electronic properties - O'Donnell, Kane; Martin, T.; Allan, N. (American Chemical Society, 2015)
Recently a lithiated C(100)-(1 × 1):O surface has been demonstrated to possess a true negative electron affinity: that is, the conduction band minimum at the surface is lower in energy than the local vacuum level. Here we present a density functional theory study of diamond surfaces with various alkali-metal- and alkaline-earth-oxide terminations. We find a size-dependent variation of electronic surface properties that divides the adsorbates into two groups. In both cases, ether bridges are broken. Adsorption of the smaller alkali metals/alkaline earths such as lithium and magnesium leads to a significant surface dipole resulting from transfer of charge across X-O-C complexes, whereas at the other extreme, cesium- and potassium-adsorbed C(100)-(1 × 1):O surfaces exhibit conventional dipole formation between the ionic adsorbate and a negatively charged carbonyl-like surface. Sodium is intermediate. Computed surface band structures and density of states are presented, illustrating the key electronic differences between these two groups.